Defusing disruptive behavior in the classroom - Colvin, Geoffrey, 1941- 4 0 16; 5 (Thousand Oaks, California : Corwin, 2010)
Describes seven behavioral principles for defusing disruptive behavior in the classroom, discusses research-based approaches to responding to various situations, and includes scenarios, checklists, and action plans.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Behavior modification. -- Classroom management.;Problem children;Emotionally disturbed children.;Behavior modification; 20; 2